Time-dependent Mechanical Response at the Nanoscale. (September 2020) - Múnera, Juan Camilo; Goswami, Debkalpa; Martinez, Ramses V.; Ossa, E. Alex
Highlights: A simple methodology to characterize and analytically model the mechanical properties of time-dependent materials at the nanoscale was proposed. One metal (Pb), and two polymers (PMMA and PS), were indented at the sub-20 nm scale using commercial atomic force microscopy (AFM) probes. The methodology can be implemented on any AFM system using commercially available probes. Abstract: Modern nanofabrication processes on metals, polymers, and ceramics often require deforming these materials at strain rates ranging ~10 1  – 10 7  s –1 . Therefore, there is a need to develop an appropriate methodology capable of measuring and predicting the effects of these deformation rates on the final mechanical response of the nanomaterial being processed. Here we report an experimental study of the indentation response of three materials with different nature and mechanical properties, but with known time-dependent mechanical responses. These materials allow validation of the findings under a wide variety of conditions. One metal (Pb), and two polymers (PMMA and PS), were indented at the sub-20 nm scale using commercial atomic force microscopy (AFM) probes. Based on our experimental findings, we also propose an analytical model for creeping solids in which their nanoscale mechanical behavior is completely described by two components: an elastic component (characterized by the Hertz contact model) and a time-dependent component (characterized by a power-law model). The proposed experimental protocol is easy to implement, and the analytical model can be extended to a large variety of materials. The ability to characterize the time-dependence of the mechanical response of different materials at the nanoscale will enable a better estimation of the effect of manufacturing processes on the properties and performance of nanomaterials.